MSE History, Transition And Development (Journal of Namibian Studies : History Politics Culture, 2023)
The establishment of the MSE in 1991 marked a pivotal transition in Mongolia's economy from centralized planning to market forces. This paper provides a succinct overview of key developments at the MSE, from launching secondary trading in 1995 and adopting electronic trading in 1998 to introducing diverse financial products including government and corporate bonds as well as stock indices. Regulatory reforms aimed to align the exchange with international standards such as implementing a Delivery versus Payment model with a T+2 settlement finality period. The analysis sheds light on the market's dynamics, challenges and impacts of global and domestic economic trends. In conclusion, the strategic role of the MSE in Mongolia's development is emphasized along with its growth potential and how ongoing reforms could shape its future trajectory.